C1GALT1 predicts poor prognosis and is a potential therapeutic target in head and neck cancer. Issue 43 (25th October 2018) - Lin, Mei-Chun; Chien, Pin-Hui; Wu, Hsin-Yi; Chen, Syue-Ting; Juan, Hsueh-Fen; Lou, Pei-Jen; Huang, Min-Chuan
Abstract Core 1 β1, 3-galactosyltransferase (C1GALT1) controls the crucial step of GalNAc-type O-glycosylation and is overexpressed in various human malignancies. However, its role in head and neck squamous cell carcinoma (HNSCC) remains unclear. Here we demonstrate that C1GALT1 expression is upregulated in HNSCC tumors and is associated with adverse clinicopathologic features. Moreover, high C1GALT1 expression predicts poor disease-free and overall survivals. C1GALT1 overexpression enhances HNSCC cell viability, migration, and invasion, which can be reversed by erlotinib. Silencing of C1GALT1 suppresses the malignant behavior both in vitro and in vivo. Mass spectrometry and lectin pull-down assays demonstrate that C1GALT1 modifies O-glycans on EGFR. Blocking O-glycan elongation on EGFR by C1GALT1 knockdown decreases EGF-EGFR binding affinity and inhibits EGFR signaling, thereby suppressing malignant phenotypes. Using molecular docking simulations, we identify itraconazole as a C1GALT1 inhibitor that directly binds C1GALT1 and promotes its proteasomal degradation, leading to significant blockade of C1GALT1-mediated effects in HNSCC cells in vitro and in vivo. Collectively, our findings demonstrate a critical role of O-glycosylation in HNSCC progression and highlight the therapeutic potential of targeting C1GALT1 in HNSCC treatment.